Survey Problematic Situation of Thai Language Reading of Chinese Students - QINGYUN, GAN; Plangsorn, Boonrat (RMUTP Research Journal Humanities and Social Sciences, 2025)
The purposes of this research were to investigate the reading problems of Thai language among Chinese students. The research population consists of 86 Chinese students enrolled in a tutoring institute in Bangkok. Samples are 40 students, were randomly selected using volunteer sampling. The research tools included a questionnaire on Thai language reading problems, data analysis through percentage analysis, mean, standard deviation, rank order, and content analysis. The research findings were the mean and standard deviation as followings. 1) The overall mean of consonant reading problems were at a moderate level ( = 3.20, S.D. = 1.16). 2) the overall mean of vowel reading problems are at a moderate level ( = 3.07, S.D. = 1.26). 3) Tone reading problems are at a moderate level ( = 3.45, S.D. = 1.30). 4) Reading problems of words with and without diacritics are at a moderate level ( = 2.93, S.D. = 1.33). 5) Homograph reading problems are at a moderate level ( = 2.58, S.D. = 1.28). 6) Reading problems of similar looking characters are at a moderate level ( = 2.64, S.D. = 1.38).